Palladium-catalyzed tandem allylic substitution/cyclization and cascade hydrosilylated reduction: the influence of reaction parameters and hydrosilanes on the stereoselectivity. Issue 41 (22nd June 2018) - Long, Peng-Wei; Xu, Jian-Xing; Bai, Xing-Feng; Xu, Zheng; Zheng, Zhan-Jiang; Yang, Ke-Fang; Li, Li; Xu, Li-Wen
Abstract : Pd-catalyzed AAA of 1, 2-bifunctional nucleophiles and one-pot tandem allylic cyclization/reduction gave corresponding heterocycle products with promising enantioselectivity in good yields. Abstract : To shed light on the influence of reaction parameters on palladium-catalyzed tandem allylic alkylation in the presence of Fei-Phos (a chiral trans -1, 2-diaminocyclohexane-derived phosphine ligand), the effect of different phosphine ligands, inorganic or organic bases, Brønsted acids, and other additives on the asymmetric palladium-catalysed alkylation of catechol with allylic diacetate was investigated. In this reaction, 2-vinyl-2, 3-dihydro-benzo[1, 4]dioxin products with promising enantioselectivity were achieved in good yields. In addition, a novel palladium-catalyzed three-component and one-pot allylic substitution/cyclization/reduction reaction assisted by methylphenylsilane was reported with good selectivity.